Cost of acute cough in Italian children - Dal Negro RW; Turco P; Povero M (Dove Medical Press, 2018)
Roberto W Dal Negro,1 Paola Turco,2 Massimiliano Povero3 1National Centre for Respiratory Pharmacoeconomics and Pharmacoepidemiology, Verona, Italy; 2Research & Clinical Governance, Verona, Italy; 3AdRes Health Economics and Outcome Research, Torino, Italy Objectives: Acute cough is the most common symptom among children in primary care, but the economic impact of cough episodes has never been investigated in Italian families.Materials and methods: A cross-sectional telephone survey was conducted on a representative sample of Italian families, randomly selected from general population. Collected data were analyzed to evaluate the economic impact of cough episodes according to, first, Italian Family Perspective and, second, National Health System Perspective (NHS-P). The costs considered in the analysis were the cost of drugs used (antibiotics, corticosteroids, antitussive drugs, and aerosol therapy) and the cost of child care during nursery/school absenteeism.Results: Six hundred four valid questionnaires were analyzed: mean age of children is 7 years (SD=3.3) and that of parents is 40 years (SD=6.2). Mean rate of cough episodes was 3.15/year, and in general, they were short lasting (94.6%, <2 weeks). Nursery/school absenteeism was mostly <7 days (63.2%), but almost 30% of respondents declared 7–15 days. The respondents’ willingness to spend out-of-pocket for an “effective remedy” against cough was an average of €20 (>€30 in 19.7% of cases). The overall economic impact on Italian families was estimated as €1,204 (SD=€88); it resulted in a cost per cough episode equal to €337, mainly due to nursery/school absenteeism (94.6%), whereas pharmaceutical expenditure was marginal (5.4%).Conclusion: Cough episodes are acute (lasting <1 week, mainly) but frequent, causing a considerable socioeconomic impact. The pharmaceutical costs are in line with parents’ willingness to pay but these costs result negligible when compared to those related to school absenteeism, generally not perceived by parents. Keywords: acute cough, acute cough in children, cough impact, cost of acute cough